2004
DOI: 10.1002/ejoc.200300676
|View full text |Cite
|
Sign up to set email alerts
|

Red‐ and Blue‐Shifts in Oligo(1,4‐phenyleneethynylene)s Having Terminal Donor−Acceptor Substitutions

Abstract: Four series of oligo(1,4-phenyleneethynylene)s (OPEs), 1−4 (a−d), each having a terminal dialkylamino group as their electron donor, were prepared by applying Sonogashira−Hagihara reactions and a protecting group strategy. To study the influence that the push−pull effect has on the long-wavelength absorption, three of the four series of OPEs contain terminal acceptor groups (CN, CHO, NO 2 ). Extending the conjugation (increasing the number of repeat units, n) lowers the energy E(n) of the electron transition i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 33 publications
9
70
0
6
Order By: Relevance
“…Computational studies actually revealed that within this series of constitutional isomers, the variance in the lowest-energy transitions is caused by differences in the HOMO (highest occupied molecular orbital) energy, which is highest in the cross-conjugated system. It became apparent, therefore, in this investigation that the correlation between the position of λ max in the UV/vis spectra and the effectiveness of different conjugation pathways is not always valid; a conclusion also reached by others [51,52]. For compounds with strong donor and acceptor moieties, the λ max in the UV/vis spectrum should only be considered as a measure of the change of the degree of CT in the transition from the ground state to the excited state, and should not be used for the study of conjugation effectiveness.…”
Section: © 2005 Iupac Pure and Applied Chemistry 77 1851-1863supporting
confidence: 50%
“…Computational studies actually revealed that within this series of constitutional isomers, the variance in the lowest-energy transitions is caused by differences in the HOMO (highest occupied molecular orbital) energy, which is highest in the cross-conjugated system. It became apparent, therefore, in this investigation that the correlation between the position of λ max in the UV/vis spectra and the effectiveness of different conjugation pathways is not always valid; a conclusion also reached by others [51,52]. For compounds with strong donor and acceptor moieties, the λ max in the UV/vis spectrum should only be considered as a measure of the change of the degree of CT in the transition from the ground state to the excited state, and should not be used for the study of conjugation effectiveness.…”
Section: © 2005 Iupac Pure and Applied Chemistry 77 1851-1863supporting
confidence: 50%
“…[18] UV-Visible absorption studies on OPE wires terminated with dialkylamino donor and cyano, formyl or nitro acceptor groups showed a competition between the extension of the chromophores and a decrease of the ICT upon increasing the number of PE repeat units. [19] More extensive photophysical studies on series of extended-TTF-OPE-pyrrolidinoC 60 , [20,21] porphyrin-OPE-pyrrolidinoC 60 [22] and 3,5-dimethyl-4-(9-anthracenyl)julolidine-OPEnaphthalene-bis(dicarboximide) systems [23] gave  values of 0.20, 0.11 and 0.23 Å -1 , respectively. Other examples include boron dipyrromethene (BODIPY)-OPE systems.…”
Section: Extensive Studies Have Focused On Covalently-linked Donor-brmentioning
confidence: 99%
“…The oligomers 2b (Figure 3b) and 2c (Figure 3c) show two maxima in their linear absorption as described earlier. 12 The corresponding | (3) | spectra show similar resonances which are again red-shifted. Figure 4 depicts our results for the DA OPEs 1a,b.…”
Section: Resultsmentioning
confidence: 82%